REALIZATION OF TRIILINGUAL EDUCATION AT THE CHAIR OF NATURAL SCIENCES - Suyundikova, Zh.T.; Kozhmukhametova, A.S.; Ungutbayeva, G.Sh. (PUBLISHINGS of Kostanay State Pedagogical University, 2017)
This article presents an analysis of the introduction of trilingual instruction at the Department of Natural Sciences of KSPI. The complex analysis of scientific research, methodical activity of teaching staff and students of natural science specialties in the implementation of the trilingual program is given.
Keywords: multilingual groups; students; trilingual program; department of natural sciences; further education